Disaster management a disaster manager's handbook - Carter, W. Nick (Asian Development Bank, 1992)
A reference and guide to those who, within governments and outside, may hold key responsibilities for dealing with disaster- to assist them in attaining standards if professionalism which will enable them to deal with day-to-day disaster management circumstances and with actual disaster situations.